Minerals and allied natural resources and their sustainable development : principles, perspectives with emphasis on the Indian scenario /: principles, perspectives with emphasis on the Indian scenario. ([2017]) - Deb, Mihir; Sarkar, Sanjib Chandra
No abstract available